Hospital at home, an innovative approach in geriatric care during the COVID-19 Pandemic - MD. Abu Bashar (Archives of Community Medicine and Public Health - Peertechz Publications, 2020)
The COVID-19 pandemic has profoundly affected the elderly people (those aged 60 years or above as per the definition by the World Health Organization) who are found to have higher rates of infection and poorer health outcomes in this pandemic compared to other age groups [1,2]. Nevertheless, elderly adults, despite having a wide range of chronic illnesses, are experiencing critically inadequate access to care as healthcare organizations are emphasizing more on patients primarily affected by COVID-19 [3,4]. Furthermore, Elderly people remain most vulnerable in this pandemic as most of the nations do not have adequate preparedness to ensure acute and chronic geriatric care in public health emergencies [4,5].